The Effect of Good Corporate Governance and Corporate Social Responsibility toward Corporate Value - Sebastianus Laurens; Ghani, Amirul Maalikul; Sugianto, Sugianto (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This study aimed to determine the effect of the size of independent commissioners, boards of directors, audit committees, institutional ownership and CSR disclosure on the value of manufacturing industry companies listed on the IDX in 2018 – 2022. This study employs a method with secondary data as the data source—methods of data collection in this study using literature or documentation studies. The sampling technique used was purposive sampling with multiple regression analysis techniques as the data analysis technique. The number of data used in this study is 175 samples. The results showed that the size of the independent board of commissioners and audit committee affected firm value, and other variables partially had no effect on firm value. In addition, simultaneously, the size of the independent board of commissioners, board of directors, audit committee, institutional ownership and CSR affect firm value.